2022
DOI: 10.3390/sym14030530
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Constraints on Spin Order Transfer in Parahydrogen-Induced Polarization (PHIP)

Abstract: It is well known that the association of parahydrogen (pH2) with an unsaturated molecule or a transient metalorganic complex can enhance the intensity of NMR signals; the effect is known as parahydrogen-induced polarization (PHIP). During recent decades, numerous methods were proposed for converting pH2-derived nuclear spin order to the observable magnetization of protons or other nuclei of interest, usually 13C or 15N. Here, we analyze the constraints imposed by the topological symmetry of the spin systems on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…For the efficient spin-order transfer (SOT) from pH 2 to a nucleus of choice, various approaches are available. ,, The highest polarization so far was achieved using fully deuterated precursors at high magnetic fields for the PHIP-SAH. , The reason is that the symmetry of interactions in the ethyl groups restricts the polarization transfer to 13 C at high fields to 50% and to about 35% at low fields . Up to now, it was not shown that deuteration of the precursor can improve (even theoretically) the polarization transfer in PHIP-SAH at low fields; the opposite was demonstrated .…”
Section: Resultsmentioning
confidence: 99%
“…For the efficient spin-order transfer (SOT) from pH 2 to a nucleus of choice, various approaches are available. ,, The highest polarization so far was achieved using fully deuterated precursors at high magnetic fields for the PHIP-SAH. , The reason is that the symmetry of interactions in the ethyl groups restricts the polarization transfer to 13 C at high fields to 50% and to about 35% at low fields . Up to now, it was not shown that deuteration of the precursor can improve (even theoretically) the polarization transfer in PHIP-SAH at low fields; the opposite was demonstrated .…”
Section: Resultsmentioning
confidence: 99%
“…RF-SOT at higher magnetic fields appears to be better way to transfer polarization in certain cases because: Heteronuclei are weakly coupled with hydrogens, so there is no efficient spontaneous polarization transfer to 2 H, 13 C and other heteronuclei; The effective spin system can be reduced to two protons and one (third) nucleus of choice, e.g., 13 C using selective deuteration 31 , 32 or selective excitation 50 , 51 . Note that because of the symmetry constraints 45 , 46 , a 100% polarization using only selective excitations in systems like ethyl pyruvate (A 3 B 2 X) is also not possible. …”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the low efficiency is not a problem with the particular MFC or molecule. Instead, it is a fundamental property that is bound to the symmetry of the spin system 45,46 . Experimentally, no more than 5% 13 C polarization was achieved with MFC for 40 mM pyruvate in an aqueous solution 35 .…”
Section: Limitations Of Current State Magnetic Field Cycling (Mfc)mentioning
confidence: 99%
“…limit the efficiency of SOT 46 , 47 . As a result, often, 100% polarization can not be achieved (even theoretically) with MFC 40 , 48 , 49 . Pulse sequences and irradiation-based SOTs are more flexible in this regard 50 – 52 , offering higher polarizations but higher hardware demands, too.…”
Section: Introductionmentioning
confidence: 99%